2020
DOI: 10.1002/pat.4950
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of chemically compound graphene oxide‐calcium pimelate on crystallization behavior, morphology and mechanical properties of isotactic polypropylene

Abstract: The combined nucleation effect of graphene oxide (GO) and calcium pimelate (CaPi) which are chemically compound together (expressed in GO − CaPi) in isotactic polypropylene (iPP) was investigated. Fourier transform infrared (FTIR), X‐ray diffraction (XRD) and thermogravimetric analysis (TGA) verified that CaPi was chemically compound with GO by chelate bonds. The crystallization behavior and crystalline morphologies of iPP nucleated with different mass ratio of GO and CaPi were investigated. The crystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The SEM observations clearly demonstrate the favorable compatibilization effect of graphene on the iPP/ABS blend. Some recent studies in the literature also demonstrated the improved dispersion of nucleating agents in iPP by using graphene 55,56 . The ABS dispersed phase of iPP/ABS/0.3G blend is the smallest and the distribution is more uniform.…”
Section: Resultsmentioning
confidence: 93%
“…The SEM observations clearly demonstrate the favorable compatibilization effect of graphene on the iPP/ABS blend. Some recent studies in the literature also demonstrated the improved dispersion of nucleating agents in iPP by using graphene 55,56 . The ABS dispersed phase of iPP/ABS/0.3G blend is the smallest and the distribution is more uniform.…”
Section: Resultsmentioning
confidence: 93%
“…under a nitrogen atmosphere. According to previous studies [46], the decomposition process of CaPim manifests in three distinct mass loss stages. The mass loss of 38.5% observed at 145-340 • C is attributed to the evaporation of crystalline-bonded water and organic molecules.…”
Section: Mechanical Behaviormentioning
confidence: 81%